PLAN DETERMINATION FOR PROMOTION MIX FOR SKETCH! - Thiasyura, Honey Gabrielle; Utami, Christina Whidya; Padmalia, Metta (Universitas Ciputra Surabaya, 2017)
Sketch! is a garment company which manufactures ready-made clothing meant for middleclass consumers between the age of 16 and 35 years. The promotion mix planning is expected to increase the company’s promotional activities and make them more effective in order to increase the company’s income and turnover. This research is a qualitative descriptive research with indepth interview. Purposive sampling is used to select respondents who are familiar with the problems in order to obtain in-depth information. The five research informants are the CEO of Sketch!, a marketing expert, a consumer, a potential consumer, and a business competitor. Research results conclude that the company can develop their promotional activities using five types of promotion mix, namely advertising, sales promotion, personal selling, public relation, and direct marketing. This research also advises the company to maintain a good relationship with the public through sponsorship and create a company website.